2018
DOI: 10.1002/smi.2820
|View full text |Cite
|
Sign up to set email alerts
|

Effects of workload on teachers' functioning: A moderated mediation model including sleeping problems and overcommitment

Abstract: This study investigated the mediating role of sleeping problems in the relationship between workload and outcomes (emotional exhaustion, presenteeism, job satisfaction, and performance), and overcommitment was examined as a moderator in the relationship between workload and sleeping problems. We conducted an empirical study using a sample of 884 teachers. Consistent with our predictions, results revealed that the positive indirect effects of workload on emotional exhaustion and presenteeism, and the negative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
1
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 49 publications
5
44
1
11
Order By: Relevance
“…One plausible explanation might be the over-representation of the personal trait “perfectionism” bordering to compulsion, previously identified in this patient group (personal communication). In combination with overcommitment in the working life as well as in the private life [44, 45] and an established sustained lack of energy due to lack of recuperation in this patient group over a long time period [3] might explain why the patients with medium fitness show a more sustained reduction of ED symptoms over time. The “commitment” with respect to physical activity “ambitions” among those ED patients with medium fitness level is more likely to correspond to their energy level and thus constitute a better prerequisite for sustainability over time.…”
Section: Discussionmentioning
confidence: 99%
“…One plausible explanation might be the over-representation of the personal trait “perfectionism” bordering to compulsion, previously identified in this patient group (personal communication). In combination with overcommitment in the working life as well as in the private life [44, 45] and an established sustained lack of energy due to lack of recuperation in this patient group over a long time period [3] might explain why the patients with medium fitness show a more sustained reduction of ED symptoms over time. The “commitment” with respect to physical activity “ambitions” among those ED patients with medium fitness level is more likely to correspond to their energy level and thus constitute a better prerequisite for sustainability over time.…”
Section: Discussionmentioning
confidence: 99%
“…Higher mental health impairment is consequently boosted. Similarly, Huyghebaert et al (2018) reported that higher workload predicted higher frequency of sleeping problems, a relationship seemingly boosted by the presence of higher levels of over-commitment.…”
Section: Theoretical Frameworkmentioning
confidence: 92%
“…Meanwhile moderating effect of social support between employee's workload and their organizational outcome cannot be ignored. Some other studies have also provided theoretical and empirical contribution from the context of workload and performance (Alsuraykh et al 2018;Avanzi et al, 2018;Baeriswyl et al, 2017;Gaillard, 2017;Ho, 2018;Huyghebaert et al, 2018;Miller et al, 2018;Prasad et al, 2018;Roster & Ferrari, 2019). Based on these arguments, the researcher concludes with the following research hypotheses; H1: Work load has a significant positive effect on employee performance.…”
Section: Employee Workload Motivation and Performancementioning
confidence: 93%